Perspektif Guru terhadap Pelaksanaan Supervisi Akademik Melalui Teknik Kunjungan Kelas di Sekolah Dasar - Widyawati, Yenny; Sutopo, Anam; Wulandari, Murfiah Dewi; Minsih, Minsih (Cetta: Jurnal Ilmu Pendidikan, 2025)
The importance of academic supervision in supporting the professional development of teachers, especially at the elementary school level, plays a crucial role in improving the quality of education. This study aims to describe teachers' perspectives on the implementation of academic supervision using classroom visitation techniques in elementary schools, as well as to understand the impact of supervision on enhancing teachers' professional competence. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews with teachers, direct observations during the implementation of academic supervision, and related documentation. Data analysis was conducted thematically to identify key patterns in teachers' understanding of academic supervision. The results show that most teachers view classroom visitation supervision as a positive form of development, but there are challenges in terms of openness and follow-up. Other challenges include time limitations, high administrative burdens, and variation in the quality of feedback from supervisors. Supervision conducted in a participatory and continuous manner has been proven to be more effective in helping teachers improve teaching methods and enhance the quality of teaching in the classroom.